Nail apparatus melanoma: dermoscopic and histopathologic correlations on a series of 23 patients from a single centre. (22nd September 2017) - Starace, M.; Dika, E.; Fanti, P.A.; Patrizi, A.; Misciali, C.; Alessandrini, A.; Bruni, F.; Piraccini, B.M.
Abstract: Background: Nail apparatus melanoma (NAM) is an uncommon tumour, and there are few studies focused on its dermoscopic features. Objective: The aims of our study were to evaluate the diagnostic accuracy of dermoscopy in NAM. A diagnostic algorithm for adult patients with suspected NAM is proposed. Methods: We collected NAM dermoscopic images of patients with a proven histopathology from 2008 until 2015. Clinical and dermoscopic images were blindly examined by two dermatologists, and correlations between histopathological aspects and dermoscopic features were investigated. Results: We retrospectively collected NAM dermoscopic images associated with a proven histopathology of 23 Caucasian patients. Only cases with available both preoperative dermoscopic images and bioptic specimens were included. Seventeen women and six men were included. The mean age at diagnosis was 63 years (range 18–92). Conclusion: We created an algorithm to indicate the correct way to follow an adult patient with suspected NAM. This algorithm may ameliorate management in case of suspected NAM and possibly facilitate an early diagnosis.